Children and youth in a new nation - Marten, James Alan (Children and youth in America., 2009)
In the early years of the Republic, as Americans tried to determine what it meant to be an American, they also wondered what it meant to be an American child. A defensive, even fearful, approach to childhood gave way to a more optimistic campaign to integrate young Americans into the Republican experiment. In this work, historians unearth the experiences of and attitudes about children and youth during the decades following the American Revolution. Beginning with the revolution itself, the contributors explore a broad range of topics, from the ways in which American children and youth participated in and learned from the revolt and its aftermaths, to developing notions of ideal childhoods as they were imagined by new religious denominations and competing ethnic groups, to the struggle by educators over how the society that came out of the Revolution could best be served by its educational systems. The volume concludes by foreshadowing future child saving efforts by reformers committed to constructing adequate systems of public health and child welfare institutions. Rooted in the historical literature and primary sources, this book is a resource in our understanding of origins of modern ideas about children and youth and the conflation of national purpose and ideas related to child development.